Assessment of Sahiyya (Accredited Social Health Activist) in relation to antenatal services: Ormanjhi, Ranchi, Jharkhand - Karir, Shilpa; Haider, Shamim; Kashyap, Vivek; Sagar, Vidya; Singh, Shashi Bhushan (International Journal Of Community Medicine And Public Health, 2017)
Background:Accredited Social Health Activist (ASHA) acts as a ‘bridge’ between the rural people and health service outlets and would play a central role, in achieving national health and population policy goals. In Jharkhand ASHA is known as “Sahiyya”. The present study was aimed to assess Sahiyyas in relation to antenatal services delivered by her in the field practice area Ormanjhi of Rajendra Institute of Medical Sciences (RIMS), Ranchi. Methods:This was a community based cross sectional study. All Sahiyyas (26), women having children under 3 years of age (196), pregnant women (140), Anganwadi workers (AWWs) (16) and Auxiliary Nurse Midwives (ANMs) (6) from the study area were recruited for the study. Assessment of antenatal services delivered by Sahiyyas was done based on interview with Sahiyyas which was then crosschecked through the responses of beneficiaries, AWWs and ANM. Results:All Sahiyyas in the study area were aware about her job responsibilities like help during registration and mobilization during pregnancy but when cross checked, 70.2% and 60.9% beneficiaries received help during registration and mobilization. Out of 336 beneficiaries, only 23.2% and 19.9% responded that were counselled by Sahiyyas on nutrition and adequate rest during pregnancy during their home visits. Conclusions:Sahiyyas were well aware of her responsibilities related to antenatal services like counselling mothers on diet, rest and other health advices through home visits but these jobs were not being done passionately by her as other incentive oriented jobs.